Radiation‐induced morphoea treated with UVA‐1 phototherapy. (30th May 2014) - Lim, D.; Johnston, S.; Novakovic, L.; Fearfield, L.
Summary Morphoea is a localized inflammatory disorder of the dermis and subcutaneous fat and radiotherapy is a rarely reported cause (estimated incidence of 2 per 1000). Morphoea is commonly mistaken for an inflammatory recurrence of breast cancer, resulting in unnecessary investigations and treatment. We report the case of a 40‐year‐old woman who developed radiation‐induced morphoea of the breast 7 months following adjuvant radiotherapy. She was treated with topical and systemic steroids as well as psoralen plus ultraviolet (UV)A before proceeding to UVA1 phototherapy. We also review the literature and discuss other management options.